Advokasi Dualisme Kebebasan Visa di Indonesia - Prasada, Dewa Krisna (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 3 (2020), 2020)
Visa is a written letter that has an element of legality used when one visits another country. In 2016 the President of the Republic of Indonesia issued a Presidential Regulation regarding Visa-Free Visit. Presidential Decree Number 21 Year 2016 concerning Visa-Free Visit (BVK) provides an opportunity for 169 countries to freely visit the territory of the Republic of Indonesia without a visa. With this provision, it creates dualism in a social environment. On one hand, this provision is beneficial in increasing the tourism economy, and on the other hand, the growth of the risk of criminalization by foreigners is increasing. This study aims to provide a solution to the problem in legal provisions to prevent and control the traffic of foreigners to Indonesia after the enactment of the BVK and how to sanction citizens who abuse the visa-free visit permit. This study uses normative legal research methods. The results of this study indicate that the rules that determine the supervision and implementation of the rules systematically against foreigners who abuse BVK are specified in Law Number 6 Year 2011, Regulation of the Ministry of Law and Human Affairs (Permenkumham) Number 17 Year 2016, and Regulation of the Ministry of Domestic Affairs (Permendagri) Number 49 Year 2010. In addition, for foreigners who are caught having committed violations, the government can provide administrative sanctions up to criminal sanctions and deportation. From the perspective of the ius constituendum, the provisions regarding BVK need to carry out legal reconstruction to determine specific sanctions against foreigners who commit violations. Besides, there is a need for provisions regarding the system for providing BVK to foreigners in detail so that it is right on target. Visa merupakan sesuatu surat tertulis yang memilki unsur legalitas yang digunakan dalam kegiatan kunjungan menuju negara lain. Pada tahun 2016 Presiden Republik Indonesia mengeluarkan Peraturan Presiden mengenai bebas visa kunjungan. Perpres Nomor 21 Tahun 2016 tentang Bebas Visa Kunjungan (BVK) memberikan kesempatan bagi 169 negara untuk bebas berkunjung ke wilayah Republik Indonesia tanpa visa. Ketentuan tersebut menimbulkan dualisme dalam suatu lingkungan sosial. Di satu sisi, ketentuan ini menguntungkan dalam peningkatan ekonomi pariwisata, dan di sisi lain pertumbuhan resiko kriminalisasi oleh orang asing kian bertambah. Kajian ini bertujuan memberikan suatu jawaban dari permasalahan dalam ketentuan hukum untuk mencegah dan mengendalikan lalu lintas orang asing ke Indonesia pasca berlakunya BVK dan bagaimana sanksi kepada warga yang menyalahgunakan izin bebas visa kunjungan. Kajian ini menggunakan metode penelitian hukum normatif (normative legal research). Hasil penelitian ini menunjukkan bahwa aturan-aturan yang menentukan mengenai pengawasan dan berjalannya aturan secara sistematis terhadap orang asing yang menyalahgunakan BVK ditentukan dalam Undang-Undang Nomor 6 Tahun 2011, Permenkumham Nomor 17 Tahun 2016, dan Permendagri Nomor 49 Tahun 2010. Selain itu bagi orang asing yang tertangkap telah melakukan pelanggaran, pemerintah dapat memberikan sanksi administratif sampai sanksi pidana dan deportasi. Dari prespektif ius constituendum ketentuan mengenai BVK perlu dilakukan rekonstruksi hukum guna menentukan sanksi secara khusus terhadap warga asing yang melakukan pelanggaran. Selain itu, perlu adanya ketentuan mengenai sistem pemberian BVK kepada orang asing secara mendetail agar tepat sasaran.